2014
DOI: 10.1063/1.4903341
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial layer on complementary resistive switching in the TiN/HfOx/TiN resistive memory device

Abstract: In-operando hard X-ray photoelectron spectroscopy study on the impact of current compliance and switching cycles on oxygen and carbon defects in resistive switching Ti/HfO2/TiN cells J. Appl. Phys. 115, 204509 (2014); 10.1063/1.4879678In-operando and non-destructive analysis of the resistive switching in the Ti/HfO2/TiN-based system by hard xray photoelectron spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Excellent agreement between the fitting and the measurement is achieved, which indicates that the equivalent circuit shown in Fig. 2 [16], [17], the resistivity is estimated to be ∼400 · cm, which is within the reported resistivity range of TiON films [18]. To examine the behavior of different high-resistance states, we conducted the complex impedance measurement after each reset process at different values of V stop , and the result is shown in Fig.…”
Section: Resultssupporting
confidence: 67%
“…Excellent agreement between the fitting and the measurement is achieved, which indicates that the equivalent circuit shown in Fig. 2 [16], [17], the resistivity is estimated to be ∼400 · cm, which is within the reported resistivity range of TiON films [18]. To examine the behavior of different high-resistance states, we conducted the complex impedance measurement after each reset process at different values of V stop , and the result is shown in Fig.…”
Section: Resultssupporting
confidence: 67%
“…The switching mechanism is associated with redistribution processes of oxygen vacancies [1,15,16] in the insulating layer whose concentration depends on value x in a HfO x film. Although the atomic layer deposition (ALD) [17][18][19] technology is generally used for HfO x layer synthesis, the ion beam sputtering deposition (IBSD) method has its own advantages. This method produces thin films with growth uniformity, reduced surface roughness and adhesion to the substrate even for films grown at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study [68] Ab-initio simulation has shown that the energy barrier for metal-ion migration in an oxide is reduced in a region with a high vacancy defect concentration [132]. below.…”
Section: Physical Mechanism Analysismentioning
confidence: 97%
“…4.6 of ref. [68]). The absence of negative set/positive reset switching in this device is a consequence of the inert Pt replacing TiN as the bottom electrode and is consistent with the common view that TiN serves as an oxygen "reservoir" which enables bipolar resistive switching [68].…”
Section: Physical Mechanism Investigation Of Self-compliance Resistivmentioning
confidence: 99%
See 1 more Smart Citation